2021
DOI: 10.3390/app12010145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on the Dry Shrinkage Cracking of Lime Soils with Different Proportions

Abstract: In this study, the reasonable aging time of lime soils with different ratios was determined to investigate the effect of aging on the internal mechanism of the dry shrinkage cracking of lime soil. To this end, the effects of aging time, lime content, and particle size on the volume crack rate, expansion and shrinkage rate, particle size distribution, and pH were analyzed using a dry–wet cycle, screening, and pH tests. In addition, the changes in the particle structure of the samples and the formation of new su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wei et al [30] concluded that the nanoparticle size and high reactivity of lime improve the properties such as compressive strength and surface hardness after slaking. Yue et al [31] determined that the volume crack and expansion shrinkage rates of the sample after the dry wet cycle initially decreased, and then stabilized with increasing aging time. Different authors have analyzed the change in physical and microstructural characteristics of lime putty with slaking time [32][33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…Wei et al [30] concluded that the nanoparticle size and high reactivity of lime improve the properties such as compressive strength and surface hardness after slaking. Yue et al [31] determined that the volume crack and expansion shrinkage rates of the sample after the dry wet cycle initially decreased, and then stabilized with increasing aging time. Different authors have analyzed the change in physical and microstructural characteristics of lime putty with slaking time [32][33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…Clay-fibers mixtures affinity and their respective properties, e.g., strength and swell behavior were investigated and deliberated in recent study [25]. The inclusion of 0.6% PP fibers in clay caused an increase in apparent friction angle (φ) from 7.3 • to 12.3 • whereas apparent cohesion decreased from 105 kPa to 78 kPa [26]. Polypropylene (PP) fibers also increased the compressive strength and ductility of clay [27].…”
Section: Introductionmentioning
confidence: 99%